Comparing results between the patients with choroidal neovascularization(CNV) in age related macula r degeneration (AMD) who had no treatment to those who - Josifova Т.; Ivanovska M.; Blazevska K.; Celeva V.; Ristova J. (SOE, 2001)
The aim of this stud is to show whether the patients with CNV in cases of AMD who underwent a LPC have a beneficial effect compared to the patients who have a natural history of the disease. Materials and Methods: In the period of 1997-1998 a clinical and fluorescein angiographical investigation was made in order to determinate the CNV in cases with AMD. A subgroup of 64 patients with extra foveolar and juxta foveolar AMD, who had initial lesion that ranged between 1 and 3 MPS disc areas was included in the study. The visual acuity(VA) ranged between finger counting and 20/100. 29 patients underwent Argon Laser Photocoagulation versus 35 who had no treatment. The follow-up period was 24 months. with monitoring of the patients every three months. Results: Persistent CNV was seen in 11/29 (37.9%) patients, and recurrent CNV occurred in 14/29 (48,2%) in the treated eyes within the follow-up period. The VA in the treated group showed that the baseline VA was maintained in 8/29 (27.5%), versus the non-treated group with 17/35 (20.5%) patients. Improvement of the VA in the treated group was seen in 4/29 (13.7%), compared to non-treated group 2/35 (5.7%). From the whole number of treated patients who had visual loss, a severe visual loss was seen in 7/17 (41.1%), while the number of the patients with severe visual loss in the non-treated group was 8/16 (50%). Conclusion: Having no big differences between the treated and non-treated group with CNV in AMD, LPC is an alternative but not a satisfactory method in the treatment of these patients.